Recent advances in switchable surfactants for heavy oil production: A review - Qi Li; Lingfei Liu; Dejun Sun; Zhenghe Xu (Energy Geoscience)
Surfactants are extensively employed in the cold production of heavy oil. However, producing heavy oil emulsions using conventional surfactants poses a challenge to spontaneous demulsification, necessitating the addition of demulsifiers for oil-water separation. This inevitably increases the exploitation cost and environmental pollution risk. Switchable surfactants have garnered much attention due to their dual capabilities of underground heavy oil emulsification and surface demulsification. This study focuses on the fundamental working principles and classification of novel switchable surfactants for oil displacement developed in recent years. It offers a comprehensive overview of the latest advances in the applications of switchable surfactants in the fields of enhanced oil recovery (EOR), oil sand washing, and oil-water separation. Furthermore, it highlights the existing challenges and future development directions of switchable surfactants for heavy oil recovery.